Electrochemical Detection of Alzheimer’s Disease Biomarker, β-Secretase Enzyme (BACE1), With One-Step Synthesized Reduced Graphene Oxide - Dey, Jhilik; Roberts, Akanksha; Mahari, Subhasis; Gandhi, Sonu; Tripathi, Prem Prakash (Frontiers in Bioengineering and Biotechnology, 2022)
β-Secretase1 (BACE1) catalyses the rate-limiting step in the generation of amyloid-β peptides that is principal component involved in pathology of Alzheimer’s disease (AD). Recent research literature shows correlation between and blood and cerebrospinal fluid (CSF) level of BACE1 with pathophysiology of AD. In this study, we report one step synthesised reduced graphene oxide (rGO), activated via carbodiimide chemistry, conjugated with BACE1 antibody (Ab) and immobilised on fluorine-doped tin oxide (FTO) electrodes for rapid detection of BACE1 antigen (Ag) for AD diagnosis. The synthesis and fabrication steps were characterised using different type of spectroscopic, X-ray analytics, microscopic, and voltametric techniques. Various parameters including nanomaterial/Ab concentration, response time, pH, temperature, and rate of scan were standardised for maximum current output using the modified electrode. Final validation was done via detection of BACE1 Ag ranging from 1 fM-1 µM with a detection limit of 0.64 fM in buffer samples and 1 fM in spiked serum samples as well as negligible cross reactivity with neurofilament Ag in buffer, spiked serum and spiked artificial CSF. The proposed immunosensor gave a quick result in 30 s, good repeatability and storage stability for a month, making it a promising candidate for sensitive, specific and early diagnosis of AD. Thus, the fabricated electrochemical biosensor for BACE-1 detection improves detection performance compared to existing sensors as well as reduces detection time and cost, signifying its potential in early diagnosis of AD in clinical samples.